The level of academic performance among UiTM Seremban 3 Students in online learning during COVID-19 pandemic / Fatin Syahiratuniza Masnorahaslenda and Nur Natasha Najwa Mohamad Saufi - Masnorahaslenda, Fatin Syahiratuniza MasnorahaslendaFatin Syahiratuniza; Mohamad Saufi, Nur Natasha Najwa (2022)
This purpose of this study was conducted to analyze the level of academic performance during COVID-19 pandemic. This study also to determine the factor that influencing academic performance of student during Covid-19 pandemic in UiTM Seremban 3. The factors observed to conduct this study were motivation of student, home environment and learning skills. This research was intended to explore the relationship of these three factors on student’s academic performance. Many previous studies on this topic were conducted and found the Covid-19 pandemic had impacts on student’s academic performance. To answer to the research question, quantitative method was used that obtained mainly from primary data which involved 357 of respondents from UiTM Seremban 3, Negeri Sembilan through online questionnaire. The result of this study found that all the three factor that mentioned above has a significant relationship with academic performance of student in UiTM Seremban 3. However, from the research findings, it was found that learning skills is the most contributing factor that influenced the academic performance of student.